Russell's Philosophy of Logical Analysis, 1897-1905 - Galaugher, J. author. aut Link
XII, 218 p.
Keywords: This systematic and historical treatment of Russell's contributions to analytic philosophy, from his embrace of analysis in 1898 to his landmark theory of descriptions in 1905, draws important connections between his philosophically motivated conception of analysis and the technical apparatus he devised to facilitate analyses in mathematics.